Spatial ecological interactions between coyote and gray fox in a temperate forest - Rodríguez-Luna, César R.; Servin, Jorge; Valenzuela-Galván, David; List, Rurik (THERYA, 2021)
Coyotes (Canis latrans) and gray foxes (Urocyon cinereoargenteus) are abundant and widely distributed in México, with no information currently available about their spatial interactions in the country. Our objectives were to evaluate the habitat use of these species and the environmental interactions between them throughout the overlapping areas of their home ranges in temperate forests of Durango, México. We expected that their coexistence would be facilitated by the spatial segregation of their ecological niche, exhibited by the low or nil overlap between their home ranges or by differentiated habitat use. Radio-collars (VHF) were attached to nine individuals â€” four coyotes (two males and two females) and five gray foxes (females) â€” that were radio-tracked from September 2017 to August 2019. We estimated their home ranges and the size of their core areas through the minimum convex polygon and determined the extent of overlap between them. Also, we evaluated third-order habitat selection and use based on habitat availability using Manlyâ€™s habitat-selection ratios and simultaneous Bonferroni confidence intervals (95 %). The mean home range size for coyotes was larger (12.2 Â± 1.74 km2) than for gray boxes (5.3 Â± 0.67 km2); the interspecific mean overlap was 42 % (moderate). Of these two canids, just the gray fox showed a markedly selective habitat use. Our findings revealed a moderate overlap between the home ranges of both canids, so spatial segregation did not occur. Although a differential habitat use was observed, explaining the coexistence between these two canids in the areas where they thrive, they tend to avoid agonistic interactions.